Effects of Tryptophan and Physical Exercise on the Modulation of Mechanical Hypersensitivity in a Fibromyalgia-like Model in Female Rats - Rezende, Rafael Marins (2024)
Though the mechanisms are not fully understood, tryptophan (Trp) and physical exercise seem to regulate mechanical hypersensitivity in fibromyalgia. Here, we tested the impact of Trp supplementation and continuous low-intensity aerobic exercise on the modulation of mechanical hypersensitivity in a fibromyalgia-like model induced by acid saline in female rats. Twelve-month-old femaleWistar rats were randomly divided into groups: [control (n = 6); acid saline (n = 6); acid saline + exercise (n = 6); acid saline + Trp (n = 6); and acid saline + exercise + Trp (n = 6)]. Hypersensitivity was caused using two intramuscular jabs of acid saline (20 μL; pH 4.0; right gastrocnemius), 3 days apart. The tryptophan-supplemented diet contained 7.6 g/hg of Trp. The three-week exercise consisted of progressive (30–45 min) treadmill running at 50 to 60% intensity, five times (Monday to Friday) per week. We found that acid saline induced contralateral mechanical hypersensitivity without changing the levels of Trp, serotonin (5-HT), and kynurenine (KYN) in the brain. Hypersensitivity was reduced by exercise (~150%), Trp (~67%), and its combination (~160%). The Trp supplementation increased the levels of Trp and KYN in the brain, and the activity of indoleamine 2,3-dioxygenase (IDO), and decreased the ratio 5-HT:KYN. Exercise did not impact the assessed metabolites. Combining the treatments reduced neither hypersensitivity nor the levels of serotonin and Trp in the brain. In conclusion, mechanical hypersensitivity induced by acid saline in a fibromyalgia-like model in female rats is modulated by Trp supplementation, which increases IDO activity and leads to improved Trp metabolism via the KYN pathway. In contrast, physical exercise does not affect mechanical hypersensitivity through brain Trp metabolism via either the KYN or serotonin pathways. Because this is a short study, generalizing its findings warrants caution.